2019
DOI: 10.5902/2236583438238
|View full text |Cite
|
Sign up to set email alerts
|

Perfil do uso de medicamentos por idosos da Estratégia Saúde da Família de Porto Alegre

Abstract: Objetivo: Avaliar o perfil farmacológico dos idosos atendidos pela Estratégia Saúde da Família (ESF). Métodos: Estudo transversal, coletado de forma prospectiva em uma amostra aleatória da população idosa cadastrada na ESF de Porto Alegre/RS. Os idosos foram entrevistados nas residências pelos agentes comunitários de saúde que aplicaram um questionário geral, contendo informações sobre medicamentos. Os dados farmacoterapêuticos foram utilizados para identificar os princípios ativos, classificados pela Anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
2
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 10 publications
4
2
0
14
Order By: Relevance
“…Regarding sociodemographic characteristics, there was a predominance of those with older age and females, as verified in other studies published in the literature 7,8,20 . These factors may also be related to the prevalence of the use of medications and groups corroborating other studies that bring the same groups, although with different percentages 7,8,20,29 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Regarding sociodemographic characteristics, there was a predominance of those with older age and females, as verified in other studies published in the literature 7,8,20 . These factors may also be related to the prevalence of the use of medications and groups corroborating other studies that bring the same groups, although with different percentages 7,8,20,29 .…”
Section: Discussionsupporting
confidence: 85%
“…In 2015, depression reached about 5.8% of the Brazilian population, above the global percentage (4.4%) of the same year 33 . The most common antidepressant medicine was fluoxetine (2%) similar to that found by Andrade et al 29 . A study conducted nationally showed that 38.8% of the drugs prescribed belonged to the class of antidepressants, highlighting fluoxetine (28.8%) 34 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Um grupo de idosos avaliados por agentes comunitários de saúde em Porto Alegre revelou a prevalência de uso para medicamentos para o sistema cardiovascular, assim como também medicamentos para o tratamento da depressão, como o floxetina, que confere um problema de saúde pública devido aos aspectos negativos consequentes do uso em idosos, tais como insônia, tonturas e confusão mental (19) .…”
unclassified